2016
DOI: 10.7322/jhgd.119275
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between the Municipal Human Development Index and rates of violent death in Brazilian Federal Units

Abstract: Because countries with the highest Human Development Index (HDI) have low rates of violence, it is common to assume that the increase of HDI may correspond with lower rates of violence in a country. This study examined the relationship between the Municipal Human Development Index (MHDI) and violent deaths in the Brazilian States between 1991 and 2010. We tested whether the increase of MHDI indirectly reduces violence or whether the reduction of violence predicts higher MHDI in later years. The raw data were o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 3 publications
0
7
0
2
Order By: Relevance
“…Although these limitations matter, confronting femicide cannot be based only on the force of laws, requiring public policies that reduce gender inequities and inequalities in all areas of society 2,7 . Furthermore, analyses indicate a relationship between the decrease in homicides and improvement in the Human Development Index (HDI) over the years in Brazil 39 .…”
Section: Discussionmentioning
confidence: 99%
“…Although these limitations matter, confronting femicide cannot be based only on the force of laws, requiring public policies that reduce gender inequities and inequalities in all areas of society 2,7 . Furthermore, analyses indicate a relationship between the decrease in homicides and improvement in the Human Development Index (HDI) over the years in Brazil 39 .…”
Section: Discussionmentioning
confidence: 99%
“…Some authors defend the hypothesis that the acceleration of human development (especially with increased income and education levels) can, in the long term, lead to a decrease in violence, and conversely, an increase in violence can hinder human development. The study by Winzer 26 analysed the relationship between human development, inequalities, proportion of poor people and violence in the Brazilian federative states, and demonstrated that this relationship is complex and that a decrease in homicides between 1991 and 2009 resulted in better municipal human development indices in 2010 26 .…”
Section: Discussionmentioning
confidence: 99%
“…The MHDI was developed by the United Nations Development Programme (UNDP) in Brazil, the Brazilian Institute for Applied Economic Research (IPEA) and the João Pinheiro Foundation based on an adaptation of the global Human Development Index (HDI) for the Brazilian municipalities' reality (Lucena et al, 2018;Winzer, 2016;Malik, 2014). The index considers the same three original dimensions of the HDI -income, longevity and education -adapting the methodology to the Brazilian context and the availability of national data.…”
Section: The Municipal Human Development Index (Mhdi)mentioning
confidence: 99%
“…The MHDI calculation methodology works in a similar way to the global HDI taking into account the three main axes: income, longevity and education, identified as standard of living, long and healthy life and access to knowledge, respectively (Winzer, 2016;Malik, 2014). Nevertheless, this indicator fails to analyze environmental variables.…”
Section: The Municipal Human Development Index (Mhdi)mentioning
confidence: 99%
See 1 more Smart Citation